Base Metal‐Catalyzed C‐Methylation Reactions Using Methanol. Issue 22 (6th October 2021) - Sarki, Naina; Goyal, Vishakha; Natte, Kishore; Jagadeesh, Rajenahally V.
Abstract: C‐methylation is a vitally important reaction applicable in chemical synthesis and structure‐based drug design. Notably, the "magic methyl" effect has become decisive in medicinal chemistry and drug discovery for the modulation of bio‐active properties in life science molecules. In this regard, C‐methylation reaction is widely applied chemical modification in various biomolecules, pharmaceuticals, and natural products. In general, this reaction often relies on activated, hazardous and uneconomical methyl sources such as diazomethane, dimethyl sulfate, and methyl halides. To achieve methylation reactions in a sustainable and cost‐effective manner, the use of 'ideal' C1 source is crucial. In this regard, methanol constitutes an expedient −CH3 source because this simple alcohol is less‐hazardous, inexpensive, and abundantly available platform chemical as well as it produces only water as the by‐product in methylation processes. Regarding potential catalysts to perform C‐methylation using methanol by hydrogen borrowing methodology, non‐noble metal‐based catalysts are highly preferable due to their unique advantages such as more abundance, inexpensive and low‐toxicity. In recent years, chemists made significant contributions towards catalytic valorization of methanol as C1 source to insert methyl groups via C−H activation in a variety of compounds and life science molecules. Consequently, in this minireview we summarize the C‐methylation process using methanol by applying Fe‐, Mn‐, Co‐ and Ni‐based catalysts as well as metal free catalysts. Abstract :